Vibration impact and noise protection devices with DVA for wheeled vehicles - Diveev, Bogdan (Видавництво Львівської політехніки, 2020)
The article investigates vibration and noise protection devices for wheeled vehicles using dynamic vibration absorbers (DVA). Algorithms for modeling their dynamic characteristics based on adaptive calculation schemes are presented. A non-linear suspension with DVA and a noise-absorbing partition is considered, which is due to the introduction of a layered composite thinwalled structure with an intermediate damping layer with high damping properties and a DVA system, which provides better vibration and noise absorption. The problems of shock propagation during the overturn of the bus to passengers are also considered. The influence of the parameters of the shock absorber on the dynamic properties of the bus is investigated. The optimal parameters of the shock absorber are determined.
Keywords: suspension; wheeled car; vibration; dynamic vibration absorber; noise barrier; bus overturn; shock absorber; optimization